Increasing Young Learners’ Islamic Education and Acquiring Language Competence Through “Madin Plus Program” at Arjowinangun Village, Pacitan Regency with a Participatory Action Research - Fitri, Okta Maya; Sinollah (Proceedings of Annual Conference on Community Engagement, 2022)
The lack of a place to accommodate activity to increase Islamic knowledge as well as enhance language competence as the same time especially since covid 19 pandemics evokes the need to make a change by engaging positive activities through “Madin Plus Program.” Madin Plus program is the first established Madin in Pacitan which combines learning Islamic education and learning English language. The curriculum in Madin Plus program is based on Ministry of Religion and the English curriculum is self-designed curriculum based on the condition of young learners. PAR method is utilized to realize this plan. The results showed that Madin Plus Program brought positive impacts to young learners and parents because this program provides learning environment that enhance students’ learning motivation. It also helps parents in educating their children not only on the religious aspect but also language aspect.